Can inhaled cannabis users accurately evaluate impaired driving ability? A randomized controlled trial - Hartley, Sarah; Simon, Nicolas; Cardozo, Bibiana; Larabi, Islam Amine; Alvarez, Jean Claude (Frontiers in Public Health, 2023)
Aims: To study the effect of inhaled cannabis on self-assessed predicted driving performance and its relation to reaction times and driving performance on a driving simulator.Participants and methods: 30 healthy male volunteers aged 18-34: 15 chronic (1-2 joints /day) and 15 occasional (1-2 joints/week) consumers. Self-assessed driving confidence (visual analogue scale), vigilance (Karolinska), reaction time (mean reciprocal reaction time mRRT, psychomotor vigilance test), driving ability (standard deviation of lane position SDLP on a York driving simulator) and blood concentrations of delta-9-tétrahydrocannabinol (THC) were measured before and repeatedly after controlled inhalation of placebo, 10mg or 30mg of THC mixed with tobacco in a cigarette.Results: Cannabis consumption (at 10 and 30 mg) led to a marked decrease in driving confidence over the first two hours which remained below baseline at 8 hours. Driving confidence was related to THC dose and to THC concentrations in the effective compartment with a low concentration of 0.11ng/ml for the EC50 and a rapid onset of action (T1/2 37 minutes). Driving ability and reaction times were reduced by cannabis consumption. Driving confidence was shown to be related to driving ability and to reaction times in both chronic and occasional consumers.Conclusions: Cannabis consumption leads to a rapid reduction in driving confidence which is related to reduced performance on a driving simulator.